Development of principles to control the processes of continuous casting of alloys using magnetodynamic equipment - Dubodelov, Viktor; Semenko, Anastasiia; Bogdan, Kim; Goryuk, Maksym (Eastern-European Journal of Enterprise Technologies, 2019)
A new principle to control the temperature and mass flow rate of metal melt at its continuous casting has been proposed. It has been established that such control can be executed based on continuous monitoring of the mass of a liquid alloy in casting and metallurgical assemblies and at appropriate adjustment by the equipment systems. Using electromagnetic fields and magnetohydrodynamic (MHD) factors to influence a liquid-metal environment is an effective means to ensure the required technological and technical-economic indicators for the process of continuous casting. We have proposed an appropriate principal structural-functional circuit for the automated control system (ACS) over the process of continuous casting of alloys, based on the application of a magnetodynamic tundish (MD-T) and a magneto-weighting system. Their basic design features and functional capabilities have been defined that are related to the processes of continuous casting, compared both with existing equipment and systems for similar purposes. It has been proposed to implement MD-T in the form of a two-chamber assembly, which separates the functions of receiving the melt from a steel-casting ladle, heating the liquid metal, releasing it into the crystallizer of a continuous casting machine (CCM). Stabilization of the flow rate mode of casting, including low-head, is achieved by permanently controlling the mass of melt in the system and by tracking its level in the release chamber of MD-T and in the crystallizer of CCM. The devised technique and created assemblies, the system, as well as auxiliary devices, would make it possible to significantly improve modern technologies of continuous casting